GE_GERICHTE P/23189/2015 vom 15. September 2016 - GE Cour de justice (2016)
CONTRAVENTION ; ACCIDENT DE LA CIRCULATION ; DISPOSITIONS PÉNALES DE LA LCR ; FIXATION DE LA PEINE ; AMENDE | CPP 398.4 ; CP 12.2 ; LCR 26.1 ; LCR 31.1 ; LCR 51.1-3 ; LCR 90.1 ; LCR 92.1 ; OCR 3 ; OCR 56 ; CP 106